Síntese e caracterização da Metilcelulose a partir da metilação heterogênea do bagaço de cana-de-açúcar - Vieira, Rose Gonçalves Português (2004)
In the present work, methylcellulose was synthesized and characterized through heterogeneous methylation, using puriﬁed sugar cane bagasse cellulose as starting material and methylsulfate as alkylating material. The produced methylcellulose was then characterized through Fourier— Transform Infrared spectroscopy (FTIR), and through chemical analysis by determining the number of methoxyl groups. The cellulosic pulp from Rhodia (Santo André — SP, obtained through the Kraft pulping process) was used as a standard during the analyses. In order to evaluate the degree of substitution (DS) obtained during the synthesis it was realized experiments without and with solvent (cetone or toluene). The methylcellulose D.S. values ranged from 0.50 to 0.70 when a solvent wasn’t used during the synthesis, while the D.S. rose up to 1.20 when performing the synthesis with solvents. Through the analysis of the absorption bands in the infrared spectrum and the results obtained through chemical determination for the DS values, a calibration curve was built for the methylcellulose. Using this calibration curve, the degree of substitution in the studied D.S. range can be obtained.